Rheological Study of Formate (Nacl) and Ethylene Glycol Based Drilling Fluid Using MATLAB - Sabiu, Bilal; Bello, Abdurrazak Ayobami; Abubakar, Habib Adebisi (Journal of Science and Technology, 2023)
Non-Newtonian models are used in describing the rheology of drilling fluids. Models, such as Power Law, Bingham Plastic, and the Hershel-Buckley model are used to predict drilling fluid behaviour. Selection of the best rheological model that accurately represents the shear stress-shear rate data is optimal in determining fluid use and predicting realistic rheological behaviour. This research is aimed at studying the best rheology model to fit collected data from sodium chloride (NaCl) and ethylene glycol (EG) based drilling fluid. The assessment utilized a total of ten sets of experimental viscometry data from laboratory-formulated drilling fluid samples A to J with the varying volume of formate sodium chloride (NaCl) and ethylene glycol (EG). Using Equations relating shear rates to shear stress, MATLAB non-linear regression approach was used to determine the best of the three rheological models to fit the experimental. The Root square (R2), Adjusted Root square (Adj R2), and Root Mean Square Error (RMSE) were used in determining the goodness of fit and degree of deviation of the experimental data. data. High concentrations of both NaCl and ethylene glycols in the formulation provide a better shear rate shear stress fit. Although the ethylene glycol presence may have account for the improved fit, as Sample E, F and G despite containing high volume of the formate NaCl, the data where not effectively fitted by the models. From the results, the power law model was the least suitable with an R2 value of 0.881-0.956, Adj R2 83-96%, and a poor RSME in the range 2-9. The Herschel-Bulkley model showed an improved fit for the fluids with an R2 0.897-0.973, Adj R2 87- 98%, and a better RSME <3. this model also shows a good shear thinning behaviour from its three parameter consistency (n) index values. The Bingham plastic model best fits the rheology of the drilling fluid data R2 0.93-0.99, Adj R2 93-98%, and RSME of <2.